P58 Chest imaging abnormalities in patients with uncontrolled rheumatoid arthritis prior to starting biological therapy. (12th November 2019) - Benjamin, A; Ward, K
Abstract : Background: RA associated interstitial lung disease (RA-ILD) is thought to occur in around half of RA patients. Updated guidelines for RA in England advise early introduction of biological disease modifying anti-rheumatic drugs(b-DMARDs) if disease control is not achieved without them. 1 TNF inhibitors(TNF-i), often the first line b-DMARDs, have been associated with serious respiratory adverse events(SRAE). There is increased mortality in RA-ILD patients given TNF-i compared to rituximab. 2 It is important to know which patients have RA-ILD. There is no consensus on screening for RA-ILD. Patients with RA-ILD may be without respiratory symptoms if joint disease limits exercise. CT chest would not usually be performed in asymptomatic patients. Chest X ray (CXR) is insensitive for lung parenchymal changes. RA patients requiring b-DMARDs have a CXR. We set out to describe CXR and CT abnormalities in this group with uncontrolled RA at the point of assessment for first b-DMARD. Methods: We identified adult RA patients assessed for first b-DMARD from 11/10/17–26/10/18. We reviewed CXR, CT, smoking status, rheumatoid factor (RhF) and anti–citrullinated protein antibody (ACPA) status. Those with abnormal CXR had a chest CT; additional CTs were performed at clinicians' discretion. Chi square and logistic regression explored predictors of abnormal CXR and CT; smoking, ACPA and RhF status were potential predictors. Results: See Table 1. Of 27 patients with an abnormal CT, 12(44%) had a normal CXR. Normal CXR was not a significant predictor of normal CT. Smoking and ACPA status were not significantly associated with CXR or CT abnormality. RhF positivity was significantly associated with abnormal CXR: χ²=6.30(1 d.f., n=80), p=0.01. There was no valid model to predict abnormal imaging (CXR or CT). Conclusion: We describe CXR abnormalities in a cohort of patients at a set point in their RA disease course. 40% of the 30 CTs performed picked up lung abnormalities missed by CXR, including RA-ILD. It is difficult to predict patients with RA-ILD from CXR; clinicians need to be aware of possible toxicity of TNF-i and have a low threshold for performing CT chest. References: NICE. NG100: Rheumatoid arthritis in adults: management. 2018. Druce KL, et al . RMD Open 2017;3(1):e000473-e.